2021
DOI: 10.1007/s10072-021-05764-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Composite Autonomic Symptom Score 31 in the German language

Abstract: Background The Composite Autonomic Symptom Score 31 (COMPASS 31) is a validated, 31-item self-assessment questionnaire assessing autonomic symptoms in six domains, orthostatic intolerance, vasomotor, secretomotor, gastrointestinal, bladder, and pupillomotor function. So far, there is no validated German COMPASS 31 version. This study aimed at developing and validating a German COMPASS 31. Methods Two autonomic experts with command of German and English ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The results confirm previous findings 3 , 6 , 7 that patient-reported autonomic symptoms are a poor predictor of objective autonomic dysfunction. Obviously other factors contributing to subjective dysautonomia should be considered such as cerebral hypoperfusion associated with hypocapnic cerebral hypoperfusion 26 and orthostatic cerebral hypoperfusion syndrome 27 as well as comorbidities including depression, anxiety, stress, fatigue, central sensitization 28 32 , and mast cell disorders 33 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results confirm previous findings 3 , 6 , 7 that patient-reported autonomic symptoms are a poor predictor of objective autonomic dysfunction. Obviously other factors contributing to subjective dysautonomia should be considered such as cerebral hypoperfusion associated with hypocapnic cerebral hypoperfusion 26 and orthostatic cerebral hypoperfusion syndrome 27 as well as comorbidities including depression, anxiety, stress, fatigue, central sensitization 28 32 , and mast cell disorders 33 .…”
Section: Discussionsupporting
confidence: 91%
“…The advantage of questionnaires include little to no cost, they are easy to administer, and do not require a specialized autonomic center. Nevertheless, symptoms are a poor predictor of dysautonomia 4 , 5 , and the lack of correlations or poor correlations between autonomic questionnaires and autonomic testing was already noted in previous smaller studies 3 , 6 , 7 . For example, the SAS validation study showed no association between the SAS and Composite Autonomic Severity Score (CASS) 8 , a validated instrument for grading autonomic failure using cardiovascular reflex and sudomotor tests, or CASS subscores 3 .…”
Section: Introductionmentioning
confidence: 76%
“…The inclusion of patients with well-defined ME/CFS and obligatory PEM, together with detailed information on clinical and laboratory findings as well as collected biosamples, is expected to significantly enhance clinical and translational research on ME/CFS and thereby improve medical care for affected patients of any age in Germany and beyond. 1 [53] Autonomic symptoms were assessed by COMPASS 31 questionnaire, considering the total score (0-100) and the scores of the six subdomains orthostatic intolerance (0-40), vasomotor (0-5), secretomotor (0-15), gastrointestinal (0-25), bladder (0-10) and pupillomotor (0-5).…”
Section: Discussionmentioning
confidence: 99%
“…The Composite Autonomic Symptom Score-31 (COMPASS-31) is a concise instrument to assess autonomic nervous system dysfunction. It comprises 31 validated items in six domains: orthostatic intolerance, vasomotor, secretomotor, gastrointestinal, bladder, and pupillomotor function, and a total score ranging from 0 to 100 [53].…”
Section: Patient-reported Outcomes Measuresmentioning
confidence: 99%
“…All participants completed the Croatian, Serbian, Slovenian and German versions of the COMPASS-31 [11,12]. The COMPASS-31 is the most widely used questionnaire for the assessment of autonomic symptoms and consists of 31 questions examining six autonomic domains: orthostatic intolerance, vasomotor, secretomotor, gastrointestinal, bladder, and pupillomotor.…”
Section: Sudomotor System Testingmentioning
confidence: 99%